Soil phosphorus cycling is modified by carbon and nitrogen fertilization in a long‐term field experiment. Issue 2 (1st February 2021) - Wang, Ye; Bauke, Sara L.; von Sperber, Christian; Tamburini, Federica; Guigue, Julien; Winkler, Pauline; Kaiser, Klaus; Honermeier, Bernd; Amelung, Wulf
Abstract: Background and aims : Phosphorus (P) is an essential element for crop growth. However, while links of P turnover in soils to carbon (C) and nitrogen (N) availability have been described, it remains to be clarified how combinations of fertilizer C and N additions affect stocks and cycling of distinct P fractions at different soil depths. The objectives of our study were (1) to assess how soil total P stocks are affected by organic amendments and N fertilization, (2) to evaluate how different soil P fractions respond to N fertilization, and (3) to verify whether N fertilization increases soil biological P cycling. Methods : We collected soil samples from a long‐term field experiment established in 1984 in Rauischholzhausen, Germany. The soil is a Haplic Luvisol and received either no organic fertilizer (NOF), farmyard manure (FYM) or a combination of organic and mineral N fertilizer (OMF). Each treatment additionally received three levels of mineral N: 0 kg ha −1  y −1 (N0), 100 kg ha −1  y −1 (N100), and 200 kg ha −1 y −1 (N200). The organic fertilizers were applied by a manure spreader and the N fertilizer (calcium ammonium nitrate) was applied in spring as top dressing by a plot fertilizer machine. We estimated stocks of P in fractions isolated by sequential P fractionation, and assessed the oxygen isotopic composition of 1 M HCl‐extractable phosphate (δ 18 OP ). Results : We found that increased organic matter (OM) addition and mineral N inputs caused significant decreases in the stocks of resin‐ and NaHCO3 ‐extractable P in the topsoil (0–30 cm). Mineral N fertilization alone resulted in significant increases in stocks of resin‐, NaHCO3 ‐, and NaOH‐extractable P in the upper subsoil (30–50 cm). These changes occurred for both inorganic and organic P. The subsoil δ 18 OP values were closer to expected equilibrium values in soil fertilized with mineral N, indicative of more intensive biological P cycling than in the treatments without mineral N inputs. Conclusions : These findings suggest that long‐term OM and mineral N fertilization promotes topsoil P losses from labile fractions by crop uptake with an enrichment of these P forms in the subsoil, and an overall increase in biological P cycling in both top‐ and subsoil horizons upon N fertilization.